La dignidad como derecho en el Sistema Interamericano de Derechos Humanos - Busso, Giuliana (2021)
The Inter-American Court of Human Rights has declared the violation of the right to dignity in various judgments based on the provisions of section 11 of the American Convention on Human Rights, whichestablishes the right to respect of honor and recognition of dignity. This section does not refer to the right to dignity explicitly, but it has been used by the aforementioned court to declare the violation of dignity as a right. Therefore, the purpose of this paper is to investigate whether the right to dignity has an object determined by the jurisprudence of the Inter-American Court of Human Rights. Consequently, the first part of this paper will address some doctrinal positions on dignity with emphasis on two authors that have proposed systematizations of the concept of dignity as a right. Then, the second part will continue with a study of the origin of section 11, which intends to determine how and why the word «dignity» was included in the aforementioned section. Subsequently, this paper will analyze the cases in which the Inter-American Court of Human Rights declared the violation of the right to dignity.